FROM INDUSTRY TO CAREER: ASSESSMENT OF INTERNSHIP EXPERIENCE ADVANTAGE FOR FUTURE CAREER READINESS IN THE HOTEL INDUSTRY - Indriani Putri Salzabilla; Putri Astri Rangkuti; Tigor Halomoan Tambunan; Feri Ferdian (Jurnal Pendidikan dan Perhotelan (JPP), 2023)
This study aims to analyze the effect of internship experience on the career readiness in the hotel industry mediated by self efficacy. The methodology used to conduct this study is quantitative with a causal associative approach. The sample was chosen using a sort of stratified random sampling. Students of class 2019, 2020, and 2021 constituted the population. The total sample of this study was 106 who had participated in the first and second internships.The independent variables in this study are internship experience and self-efficacy and the dependent variable is future career readiness. The method used in this study was quantified using two data analysis techniques, i.e. descriptive statistical analysis techniques for identifying and describing data from respondents' answers to questionnaires and inferential statistical analysis techniques using SEM (structural equilibrium modeling) data analysis methods using the PLS (partial least square) approach. SmartPLS 3 application. The results showed that internship experience affected the students future career readiness and self efficacy in the hotel industry. Self efficacy affected the future career readiness and mediated its relationship with internship experience.